Evolution of myocardial tissue injury over a decade after ST-elevation myocardial infarction: a cardiac magnetic resonance study. (13th July 2021) - Mayr, A; Klug, G; Reindl, M; Tiller, C; Holzknecht, M; Lechner, I; Pamminger, M; Troger, F; Bauer, A; Reinstadler, SJ; Metzler, B
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Austrian Society of Cardiology Background: In patients with first ST-elevation myocardial infarction (STEMI), the evolution of myocardial tissue injury parameters over a decade as assessed by cardiac magnetic resonance (CMR) has not yet been described. Purpose: This study examined long-term myocardial tissue injury dynamics in STEMI patients treated with primary percutaneous coronary intervention (PCI), as well as its association with patient characteristics. Methods: A total of 104 patients with STEMI were included in this observational study. Sequential late gadolinium enhanced CMR studies (after 3 days [interquartile ranges (IQR) 2-4], 4 months [IQR 4-5] and 9 years [IQR 8-10]) were conducted to assess left ventricular (LV) dimensions and function, infarct size and microvascular obstruction (MVO). T2* mapping was added at 9 year scan to assess the presence of persistent iron within the infarct core. Results: Infarct size decreased progressively from 13% of LV myocardial mass [IQR 7-21] to 10.2% [IQR 5.2-16.1] to 8% [IQR 2.4-12.3] (p < 0.001), with an average reduction rate of 6.4% ± 3.4 per year. Relative reduction of infarct size from baseline to 9y follow-up was 43% [IQR 18-66], 21% [IQR 3-42] during the first 4m and 33% [IQR 8-54] between 4m and 9y after STEMI. Decrease of infarct size was associated with greater baseline infarct size (p < 0.004) and extent of MVO (p = 0.01). MVO was present in 60% (60/104) of patients at baseline, but in none of the follow-up examinations. Sixteen patients had persistent iron within the infarct core at 9 year CMR. Clinical and imaging associates of persistent iron included younger age at study inclusion (p = 0.036), higher peak hs troponin T (p < 0.001), higher peak creatine kinase (p < 0.001) and higher peak CRP (p = 0.036) as well as greater infarct size at any occasion (all p < 0.001) and greater MVO (p < 0.001). Patients with persistent iron showed less relative infarct size regression (51% [IQR 41-79] versus 46% [IQR 32-54], p = 0.009). Conclusion: In patients with STEMI, the evolution of infarct size is a dynamic process that extends well beyond the first few months after the acute event. MVO vanishes in the first few weeks after the index event in all patients. However, persistence of iron within the infarct core occurs up to a decade after reperfused STEMI, reflecting its irreversibility and is associated with the initial infarct severity and worse infarct healing.